Biopolymers Online 2003
DOI: 10.1002/3527600035.bpol8013
|View full text |Cite
|
Sign up to set email alerts
|

Extra‐Organismic Adhesive Proteins

Abstract: Introduction Occurrence Barnacles Algae Mussels Molecular Genetics Functional Biomechanics Measurement of Adhesion Strength Applications of Mussel Adhesive Proteins Mucoadhesion and Surface Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 104 publications
0
13
0
Order By: Relevance
“…2 Waite and coworkers discovered that the byssal thread is composed primarily of specialized collagen proteins (PreCol proteins) that contain domains with a high content of histidine (13–19 %) and sequence homology amongst species. 58 Histidine, an amino acid that is often involved in metal ion coordination in proteins, is hypothesized to bind metal ions such as Zn 2+ and Cu 2+ in the byssal thread, whereupon the metal coordination bond is thought to break under applied load, serving as an energy dissipating mechanism. 9 Unlike most covalent bonds whose rupture is generally irreversible, coordinate bonds are capable of reforming after rupture, i.e., functioning as sacrificial bonds.…”
Section: Introductionmentioning
confidence: 99%
“…2 Waite and coworkers discovered that the byssal thread is composed primarily of specialized collagen proteins (PreCol proteins) that contain domains with a high content of histidine (13–19 %) and sequence homology amongst species. 58 Histidine, an amino acid that is often involved in metal ion coordination in proteins, is hypothesized to bind metal ions such as Zn 2+ and Cu 2+ in the byssal thread, whereupon the metal coordination bond is thought to break under applied load, serving as an energy dissipating mechanism. 9 Unlike most covalent bonds whose rupture is generally irreversible, coordinate bonds are capable of reforming after rupture, i.e., functioning as sacrificial bonds.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, an earlier study also concluded this for the mechanical properties of byssal threads from Mytilus complex species. 31 …”
Section: Methodsmentioning
confidence: 99%
“…have life histories that depend on their secure attachment to solid substrates for survival. These organisms produce and secrete adhesive proteins that form permanent, strong, and flexible underwater bonds to a variety of substrates, such as glass, Teflon, metal, and plastic 4–6. Likewise, algae are known for their ability to settle, adhere, and proliferate on virtually any exposed surface 6.…”
Section: Introductionmentioning
confidence: 99%